The Proposal for an Indo-Pacific Treaty of Friendship and Cooperation: A Critical Reassessment - Ram, Vignesh (JAS (Journal of ASEAN Studies), 2015)
The emergence of the Indo- Pacific construct brings about interesting avenues for cooperation among states in the region. Characterised by the intertwining geographies of the Indian and the Pacific Oceans, the Indo- Pacific region is home to some of the most diverse peoples and economies in the world. In a speech delivered at the CSIS, Washington in 2013, the former Indonesian Foreign Minister Marty Natalegwa outlined the need for an â€œIndo- Pacific Treaty of Friendship and Cooperationâ€. In efforts to continue to address the prospects and challenges for a treaty among the major powers in the Indo- Pacific region, the article argues that a treaty would be necessary step and but should be concluded when sufficient groundwork for it is concluded. The article also argues that, the Indo â€“ pacific concept would be best addressed if there is increased institutionalization of the concept and increased cooperation among middle powers such as India, Indonesia and Australia.